2023
DOI: 10.1002/lary.30876
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Citation Ratio: An Impartial Assessment of Productivity in Academic Otolaryngologists

Abstract: ObjectivesQuantification of academic productivity relies on bibliometric measurements, such as the Hirsch index (h‐index). The National Institutes of Health (NIH) recently developed the relative citation ratio (RCR), an article‐level, citation‐driven metric that compares researchers with others within their respective fields. Our study is the first to compare the usage of RCR in academic otolaryngology.Study DesignRetrospective Database Review.MethodsAcademic otolaryngology residency programs were identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…32,34,35 Previous studies have shown that bibliometrics including the h-index and RCR are positively correlated with academic promotion and career duration. 3,6,8,34 Our study similarly demonstrated an association between both the h-index and w-RCR and academic rank, and the h-index and career duration. Full professors had higher h-index and w-RCR scores than associate and assistant professors.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…32,34,35 Previous studies have shown that bibliometrics including the h-index and RCR are positively correlated with academic promotion and career duration. 3,6,8,34 Our study similarly demonstrated an association between both the h-index and w-RCR and academic rank, and the h-index and career duration. Full professors had higher h-index and w-RCR scores than associate and assistant professors.…”
Section: Discussionsupporting
confidence: 71%
“…Otologists receiving NIH funding were more likely to have a master's degree (18.3% vs. 8.2%, p = 0.020) or PhD (31.0% vs. 7.2%, p < 0.001) than those not receiving NIH funding. Otologists receiving NIH funding had significantly greater median (interquartile range [IQR]) h-index (25 vs. 11 [7][8][9][10][11][12][13][14][15][16][17]), m-RCR (1.6 [1.3-2.2] vs. 1.2 [0.9-1.7]), and w-RCR (105.4 [55.7-175.1] vs. 26.6 [12.2-61.8]) than those not receiving NIH funding (all p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations